Serological responses to Neospora caninum in experimentally and naturally infected water buffaloes (Bubalus bubalis) - Rodrigues, AAR; Gennari, S. M.; Paula, VSO; Aguiar, D. M.; Fujii, T. U.; Starke-Buzeti, W.; Machado, R. Z.; Dubey, J. P. (Elsevier B.V., 2005)
The water buffalo (Bubalus bubalis) is an important natural host for Neospora caninum. Serologic responses to N. caninum were studied in experimentally and naturally infected water buffaloes in Brazil. Antibodies were assayed by the indirect fluorescent antibody test (IFAT) using a cut off value of 1:25. Six buffaloes were each inoculated subcutaneously with 5 x 106 live culture-derived tachyzoites of the cattle Illinois strain of N. caninum, and two calves were kept as uninoculated controls. Post-inoculation (p.i.) blood samples were collected weekly for 8 weeks and then monthly until 1 year p.i. All inoculated buffaloes developed IFAT titers of 1:100 or more between 7 and 11 days p.i. and the titers remained elevated until 7 weeks p.i. Antibody titers peaked to 1:1600 in 1, 1:800 in 3 and 1:400 in 2, usually by 3 weeks p.i. Antibody titers declined to 1:25 or 1:50 in all the six buffaloes by 12 months p.i. IFAT titers to N. caninum remained at an undetectable level (< 1:25) in both control uninoculated buffaloes. To follow the dynamics of N. caninum antibodies, sera from 29 buffaloes and their calves were collected for 1 year and assayed for N. caninum antibodies; 23 of 29 calves were seropositive (IFAT of 1:100 or more) at 1-2 day of age. of these 23 calves, 17 remained seropositive during the study, while six became seronegative at four (two calves), six (one calf) seven (two calves) and eight (one calf) months of age. These findings suggest a high rate of neonatal transmission of N. caninum in buffaloes. Published by Elsevier B.V.
Keywords: Neospora caninum; water buffaloes; Bubalus bubalis; congenital transmission; antibodies; experimental; natural